Enviromental Health Risk Analysis of Lead (PB) Exposure to Traffic Volunteers at Inspeksi Pam road Makassar City - Sri Wahyuningsih; Nurhidayah (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
Environmental Health Risk Analysis (ARKL) Aims to estimate the risks that will occur. Lead is one of the air pollutant substances produced from vehicle exhaust emissions. The purpose of this study was to estimate the risk of exposure to lead (Pb) to parking attendants on Inspeksi PAM road Makassar City. This Research Method is Quantitative by Using Observational Method with Environmental Risk Analysis Approach (ARKL). The survey was conducted during January-March 2020, with a total of 3 respondents. Result of the study it was shown that the highest concentration of Pb was at point 1 at the T-junction of Inspeksi PAM road and Abdullah Daeng sirua road where the measurement results in the morning were 0.396 µg /Nm3 and during the day is 0.469 µg/Nm3, the Inhalation Rate for Traffic Volunteers is 0.83 m3/hour, and the safe concentration of Lead (Pb) for respondents for a body weight of 40 kg with a duration of exposure for 2 years is 0.46 mg /m3. The conclusion of this study is that Traffic Volunteers who are on Inspeksi PAM road do not have a carcinogenic risk where RQ< 1 is obtained.